RESPONSE OF LYMPHOID CELLS TO REGULATORY SIGNAL OF INTERLEUKIN 1 AS AN INDEX OF LYMPHOCYTE ACTIVITY - S. N. Shanin (SPb RAACI, 2019)
Intensivity of lymphocyte proliferative activity is an important and almost the only indicator of the level of functional activity of these cells, and the immune system in general. The aim of this study was to develop an adequate physiological test to determine the degree of functional activity of lymphoid cells. The choice of IL-1 as an activator of proliferation is justified by the presence of receptors to IL-1 on lymphoid cell membranes, the key role of this cytokine in the initiation of a wide range of biological effects of the immune system to antigen, including participation in intercellular cooperation and distant action on various cells. It was found that the ligand-receptor interaction of IL-1 by type I receptor activates neutral sphingomyelinase, and the sphingomyelin pathway of signal transduction in lymphocytes. The degree of activation of this enzyme depends on the type of stress and correlates with changes of the vector of humoral immune response and proliferative activity of lymphocytes. The level of IL-1 increases, but the activity of neutral sphingomyelinase and lymphoid cell proliferation is significantly reduced after applications of immunosuppressive stress in mice and rats. The change of the degree of lymphocyte proliferation has become a marker of the severity of the pathological process in clinic. A high degree of correlation between the low intensity of peripheral blood lymphocyte proliferation in response to IL-1 action and the unfavorable disease outcome in patients with severe combined trauma and children with purulent meningitis was established. Thus, the degree of lymphocyte proliferation in response to the action of the regulatory signal of IL-1 can be used both for the analysis of the effectiveness of immunomodulators, and as diagnostic and prognostic indicator in clinical practice.